Detection and treatment of proximal caries lesions: Milieu-specific cost–effectiveness analysis. Issue 6 (June 2015) - Schwendicke, Falk; Paris, Sebastian; Stolpe, Michael
Abstract: Objectives: Dental caries lesions are highly prevalent, concentrated in high-risk groups, and often affect proximal tooth surfaces. Choosing a caries detection method determines the available treatment options: radiographically detected early lesion stages might receive non-, micro-, or invasive treatments, whilst visually tactile detected lesions are often advanced and mostly require invasive treatment. Thus, the choice of detection method impacts on patients via the applied treatment. We compared the cost–effectiveness of combinations of detections and treatments of proximal lesions in different populations which did or did not receive prevention during adolescence. These cost–effectiveness comparisons of different detection-treatment combinations should aid clinical decision making and improve resource allocation. Methods: A Markov-model was constructed to follow a proximal posterior surface in a 12-year-old German over his lifetime. Prevalence, validity and transition probabilities were extracted from the literature. Microsimulations were performed to evaluate costs (Euro) per tooth-retention-time (years). Results: For populations with low risk, radiographic detection plus non-invasive treatment without (270 Euro, 61.5 years) and with prevention (312 Euro, 63.0 years), as well as radiographic detection plus micro-invasive treatment and prevention (373 Euro, 64.0 years) were cost-effective. For populations with high risk, radiographic detection plus micro-invasive treatment without (427 Euro, 58.5 years) and with prevention (436 Euro, 61.0 years) were cost-effective. Combinations involving invasive treatments had limited cost–effectiveness. Conclusions: Caries detection methods should be evaluated regarding the cost–effectiveness resulting from their use in different populations. Clinical significance: Caries detection methods are usually evaluated regarding their validity compared to a gold standard. We demonstrate that the cost–effectiveness stemming from using different detection methods additionally depends on the treatment options determined by different methods, and the examined population. Dentists' choice of a detection method should not only be guided by its validity, but also by its specific benefits in different populations.